2019
DOI: 10.1038/s41598-019-45589-y
|View full text |Cite
|
Sign up to set email alerts
|

HER3 targeting potentiates growth suppressive effects of the PI3K inhibitor BYL719 in pre-clinical models of head and neck squamous cell carcinoma

Abstract: BYL719 is a PI3K inhibitor that has demonstrated efficacy in the treatment of head and neck squamous cell carcinoma. BYL719 exerts its therapeutic effect by suppressing AKT and other proliferative signaling mechanisms. Despite PI3K inhibition and AKT suppression, residual activity of protein S6, a core marker of proliferative activation, has been observed. HER3, either via dimerization or activation by its ligand neurgeulin (NRG), is known to activate PI3K. Thus, we hypothesized that co-targeting HER3 and PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In the preclinical study of HNSCC, alpelisib was shown to overcome cetuximab resistance in HNSCC ( 25 ). In addition, alpelisib treatment reduced Akt activation and suppressed tumor growth in HNSCC, in vitro and in vivo ( 25 , 26 ). In the present study the HSC-3 OSCC cell line were found to be sensitive to the anti-proliferative effects of alpelisib.…”
Section: Discussionmentioning
confidence: 99%
“…In the preclinical study of HNSCC, alpelisib was shown to overcome cetuximab resistance in HNSCC ( 25 ). In addition, alpelisib treatment reduced Akt activation and suppressed tumor growth in HNSCC, in vitro and in vivo ( 25 , 26 ). In the present study the HSC-3 OSCC cell line were found to be sensitive to the anti-proliferative effects of alpelisib.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our findings highlight the likelihood that the factors governing the acquisition of resistance in HNC HPV+ may be distinct from those in HNC HPV− . While, in HNC HPV− , expression of RTKs increases following PI3K treatment [ 20 , 58 , 59 , 60 , 61 ], in HNC HPV+ , tumor cells acquire resistance to isiPI3K by the secretion of IGF2 to activate IGF1R. Our results provide the first evidence that blocking the IGF2/IGF1R pathway in combination with isiPI3K is a promising therapeutic strategy for treating HNC HPV+ patients.…”
Section: Discussionmentioning
confidence: 79%
“…Different molecular paths can lead to isiPI3K resistance, including sustained activation of mTORC1 [ 21 , 54 , 55 ], PDK1/SGK1 [ 56 ], and MYC [ 57 ]. In HNC HPV− , acquisition of resistance to isiPI3K is driven by increased activity of receptor tyrosine kinases (RTK), like EGFR [ 20 , 58 ], AXL [ 20 , 59 , 60 ], and HER3 [ 61 ], which signal through AKT or RAS/ERK pathways, or by activation of RTKs downstream of ERK/TSC2 [ 61 ], p85 [ 62 ], and CDK4/6 [ 63 ]. While, in HNC HPV− , different mechanisms of resistance to isiPI3K have been well documented by us and by others, in HNC HPV+ , only innate resistance to isiPI3K has been reported [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following 24 h of treatment with alpelisib, we observed a significant reduction in the proportion of proliferating (S-phase) cells (Fig. 1 b) [ 24 , 25 ]. To determine whether alpelisib was also able to induce cell death through apoptosis, we examined PARP cleavage (Fig.…”
Section: Resultsmentioning
confidence: 99%